The Oxford handbook of the sociology of religion - Clarke, Peter B. (Oxford handbooks in religion and theology, 2009)
The Oxford Handbook of the Sociology of Religion draws on the expertise of an international team of scholars providing both an entry point into the sociological study and understanding of religion and an in-depth survey into its changing forms and content in the contemporary world. The role and impact of religion and spirituality on the politics, culture, education and health in the modern world is rigorously discussed and debated. The study of the sociology of religion forges interdisciplinary links to explore aspects of continuity and change in the contemporary interface between society and religion. Using a combination of theoretical, methodological and content-led approaches, the fifty-seven contributors collectively emphasise the complex relationships between religion and aspects of life from scientific research to law, ecology to art, music to cognitive science, crime to institutional health care and more. The developing character of religion, irreligion and atheism and the impact of religious diversity on social cohesion are explored. An overview of current scholarship in the field is provided in each themed chapter with an emphasis on encouraging new thinking and reflection on familiar and emergent themes to stimulate further debate and scholarship. The resulting essay collection provides an invaluable resource for research and teaching in this diverse discipline.